1997
DOI: 10.1089/hum.1997.8.17-2103
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant E1-Deleted Canine Adenoviral Vector Capable of Transduction and Expression of a Transgene in Human-Derived Cells andIn Vivo

Abstract: Human adenovirus (HAV) serotypes 2 and 5 are commonly used as vector backbones for adenovirus-mediated gene transfer. However, HAVs were chosen as a backbone for the vectors for historical reasons and have a number of significant disadvantages when used as a shuttle for gene transfer in humans. As an initial trial to circumvent some of the shortcomings of HAV vectors, we have produced an E1-deleted canine adenovirus type 2 (CAV-2) vector for gene transfer. Initially, we demonstrated that CAV-2 undergoes an abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 28 publications
0
74
1
1
Order By: Relevance
“…[25][26][27][28][29][30] The immunocompetent breast cancer mouse model described in this paper could be a useful tool for testing circumvention of vector-specific immunity by alternative administration of human and non-human adenoviral vectors targeting EphA2. It will also offer an excellent model for preclinical testing of other gene therapy approaches where the vector entry into breast cancer cells is targeted through EphA2-specific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] The immunocompetent breast cancer mouse model described in this paper could be a useful tool for testing circumvention of vector-specific immunity by alternative administration of human and non-human adenoviral vectors targeting EphA2. It will also offer an excellent model for preclinical testing of other gene therapy approaches where the vector entry into breast cancer cells is targeted through EphA2-specific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that almost all subjects tested (from North America) have immunoglobulins to adenovirus type 5 of which 55% were neutralizing. 15 In addition to adenovirus type 5, serotypes 2, 7 and 17 of human adenovirus 16,17 and animal adenoviruses 18,19 have been used as vectors for studies of gene transfer. It is hypothesized that neutralizing antibodies directed against the knob and fiber domains of the viral capsid play a significant role in blocking infection.…”
Section: Adenovirus Vectorsmentioning
confidence: 99%
“…The nonhuman AdV do not cause disease in humans and are not neutralized by the HAdV-specific neutralizing antibodies (Moffatt et al, 2000;Sharma et al, 2010;Singh et al, 2008). In addition, nonhuman AdV vectors have been shown to transduce human cells in culture and express transgene (Bangari et al, 2005;Bangari & Mittal, 2004;Farina et al, 2001;Klonjkowski et al, 1997;Mittal et al, 1995;Rasmussen et al, 1999). Advances in the past decade signify the potential of nonhuman AdV vectors as effective gene delivery vehicles without any significant toxicity and interference from pre-existing immunity.…”
Section: Non-human Ad Vectorsmentioning
confidence: 99%